Pengaruh Kualitas Layanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Pengguna Ojek Online X - Muhamad Yusuf Alwi; Ryna Parlyna; Nurdin Hidayat (Jurnal Bisnis, Manajemen, dan Keuangan, 2021)
This study is to determine the effect of Service Quality on Customers, Customers on Loyalty, Service Quality on Customer Loyalty. The data were processed using a survey method with a Likert-type collection tool, the sampling technique used was purposive sampling to 200 respondents. This research was conducted on students of the Faculty of Economics, Jakarta State University. Using two factor analyzes, namely EFA (Exploratory Factor Analysis) and CFA (Confirmatory Factor Analysis), using SPSS and SEM applications on AMOS. The results of this study indicate that there is a positive and significant influence between Service Quality on Customers, there is a positive and significant influence between customers on Customer Loyalty, besides that there is also a positive influence between Service Quality and Customer Loyalty.